2020
DOI: 10.1111/mec.15347
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic processes underlying rapid adaptation of a natural Chironomus riparius population to unintendedly applied experimental selection pressures

Abstract: Evolve and Resquence (E&R) studies are a useful tool to study genomic processes during rapid adaptation, e.g., in the framework of adaptive responses to global climate change. We applied different thermal regimes to a natural Chironomus riparius (Diptera) population in an E&R framework to infer its evolutionary potential for rapid thermal adaptation. We exposed two replicates to three temperatures each (14°C, 20°C and 26°C) for more than two years, the experiment thus lasting 22, 44 or 65 generations, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 74 publications
(128 reference statements)
2
31
0
Order By: Relevance
“…An interesting comparison with our results is an E&R study of Chironomus riparius populations which shared the same genomic response despite having evolved under different temperature regimes (Pfenninger & Foucault, 2020). In this study, we also identified some gene expression changes common to both temperature regimes (Figure 3), highlighting the impact of laboratory environment on expression levels.…”
Section: Discussionsupporting
confidence: 71%
“…An interesting comparison with our results is an E&R study of Chironomus riparius populations which shared the same genomic response despite having evolved under different temperature regimes (Pfenninger & Foucault, 2020). In this study, we also identified some gene expression changes common to both temperature regimes (Figure 3), highlighting the impact of laboratory environment on expression levels.…”
Section: Discussionsupporting
confidence: 71%
“…Its genome was recently sequenced and annotated, enabling more complex genomic studies (Oppold et al, 2017; Schmidt et al, 2020). Moreover, it is known that C. riparius can rapidly adapt to environmental stress (Nowak et al, 2009; Pfenninger and Foucault, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all such efforts are so successful. In fact, a recent, very similar article recently published in Molecular Ecology concluded that E&R results from experiments with the harlequin fly ( Chironomus riparius ) were not relevant to the study of thermal adaptation in natural populations of this species (Pfenninger & Foucault, 2020). Here, the authors found no evidence of temperature‐specific changes in patterns of genetic variation across selection treatments (control, intermediate and high temperature) and concluded their study could not provide direct insights into the potential for thermal adaptation in natural C. riparius populations.…”
Section: Figurementioning
confidence: 99%
“…Perhaps laboratory evolution experiments fail to comprehensively mimic the environments that natural populations encounter. Pfenninger and Foucault (2020) sought to use experimental evolution to assess the evolutionary potential for rapid thermal adaptation in natural C . riparius populations, but the general laboratory environment proved a much stronger selective agent than any of the thermal treatments.…”
Section: Figurementioning
confidence: 99%